From Medical to Human-Rights Norms: Examining the Evolution of Trans Norms in the Netherlands - Soto-Lafontaine, Melisa (2020)
Examining the dynamics underpinning the evolution of trans norms in the Netherlands, from their emergence there in 1952 up until 2019, this article traces their development through four historical phases, each marked by notable milestones and supported by different sets of frames, actors, and norm-change mechanisms. My analysis shows that the normative profile of trans issues in the Netherlands has long been ruled by medical frames, but the last decades have also witnessed the emergence and establishment of a new set of frames rooted in human-rights discourses. By tracing the trajectory of trans norms in the Netherlands and examining the mechanisms underlying the emergence and changes of frames, this article contributes to the theoretical body of studies on norm diffusion by introducing the role of hybrid entrepreneurs, the dynamic co-assembling of medical and legal domains and the self-lead trans emancipation as a social entrepreneurial strategy.